Knowledge concerning employees’ legal rights at work among banking employees in Malaysia - Omar, Zoharah; Chan, Kit Yeen; Joned, Rusinah (Springerlink, 2009)
This study was conducted to determine the level of knowledge concerning employee rights under the Employment Act, Trade Unions Act and Industrial Relations Act among banking employees in Malaysia. This study also identified the specific areas of employee rights that employees are most familiar with and compared this level of knowledge by gender, age, tenure, and level of education. The findings revealed that the respondents do not possess sound knowledge of their legal rights. The respondents have the highest level of knowledge on employee basic rights, and have the lowest level of knowledge on rights to termination and dismissal. There was a small difference in the level of knowledge between male and female; however the level of knowledge increases with employes’ age, tenure and level of education.